VD_FINDINFO Jug / 2020 / 461 vom 8. Juni 2020 - VD Tribunal cantonal (2020)
LOI FÉDÉRALE SUR LES FORÊTS, DÉFRICHEMENT, PRESCRIPTION, ACTION PÉNALE, INTENTION, PRINCIPE DE L'ACCUSATION | 106 CP, 12 al. 2 CP, 47 CP, 98 CP, 9 CPP (CH)